Antisemitism Studies (JSTOR)
A double blind peer-reviewed academic publication, issued twice a year, Antisemitism Studies provides the leading forum for scholarship on the millennial phenomenon of antisemitism, both its past and present manifestations. Multidisciplinary and international in scope, the journal will publish a variety of perspectives on, and interpretations of, the problem of antisemitism and its impact on society.
Keywords: Jewish Studies